Randomised feasibility study to compare the use of Therabite® with wooden spatulas to relieve and prevent trismus in patients with cancer of the head and neck. Issue 4 (May 2018) - Lee, R.; Yeo, S.T.; Rogers, S.N.; Caress, A.L.; Molassiotis, A.; Ryder, D.; Sanghera, P.; Lunt, C.; Scott, B.; Keeley, P.; Edwards, R.T.; Slevin, N.
Abstract: Our aim was to compare the efficacy of the Therabite ® jaw motion rehabilitation system (Atos Medical) with that of wooden spatulas to relieve and prevent trismus in patients who have had radiotherapy for stage three and four oral and oropharyngeal cancer. Secondary aims were to assess the feasibility and the impact of exercise on health-related quality of life (QoL), and the use of health services after treatment. We designed a randomised, open-label, controlled, three-centre feasibility study to compare the effectiveness and cost of the Therabite ® and wooden spatulas. We studied compliance with exercises and health-related QoL, assessed cost using three health economics measures, and conducted semistructured interviews with patients. Patients were randomised into two groups: the Therabite ® group (n = 37) and the wooden spatula group (n = 34). All patients had some sense of jaw tightening before the study started. Mean mouth opening after six months increased in both groups, but the difference between the groups was not significant (p = 0.39). Completion rates for the three economic measures were good. There was no significant difference between the two groups in frequency of contact with care services or in QoL. Exercises during and after radiotherapy can ameliorate trismus in patients with stage three and four oral and oropharygeal cancers, but differences between groups in efficacy, compliance, QoL, or use of hospital or community health services, were not significant.